Investigation of Thermal Runaway in Prismatic Batteries with Dual-Parallel Jelly-Roll Architecture Under Thermal Abuse Conditions - Jinmei Li; Dong Li; Xin Li; Ting Sun; Qiang Li (Batteries)
In response to the increasingly serious global warming crisis, new energy batteries have progressively replaced highly polluting primary energy sources. Lithium-ion batteries (LIBs) are widely implemented due to their high safety and energy density. Although LIBs exhibit enhanced safety features, significant fire risks persist during thermal runaway (TR) events occurring in charging/discharging processes. To elucidate dual-parallel jelly-roll architecture TR characteristics of LIBs under varied operational conditions, this study integrates theoretical analysis with experimental methods, conducting thermal abuse tests under four distinct working conditions: open circuit, constant-current charging, constant-voltage charging, and discharging. The results demonstrate substantial differences in TR characteristics across operational conditions. A thermodynamic equilibrium-based triggering model proved capable of qualitatively evaluating TR risk levels under these conditions. Furthermore, the established TR triggering model reveals that the intensified Joule heating and polarization effects during constant-current charging account for its elevated fire risk compared to other states. These findings provide operational guidelines for optimizing safety strategies in energy storage power stations.